O Passeio Público do Rio de Janeiro: Análise Histórica com Auxílio da Representação Gráfica Digital - Vilas Boas, Naylor Barbosa (Paisagem e Ambiente, 2000)
The present article has the purpose to show a brief historical analysis of Passeio Publico of Rio de Janeiro, one of the most important city's public garden of 19th century originally conceived by mestre Valentim da Fonseca e Silva, a famous colonial Rio artist, by the end of 18th century With modern virtual reconstruction and eietronic modeling resources, based on intense iconographicai researches and analysis of old travelers reports, it was recreated the two main moments of the garden through those two centuries of existence: the original Passeio Publico of mestre Valentim and the one transformed by the romantic reformation of 1860's conceived by Auguste Giaziou. Originally a part of a work that studies questions of space perception analysis, the use of virtual reconstruction resources shows that it is an important tool to recreate spaces that doesn't exists fisicaiiy anymore, allowing the simulation of the perceptions experienced by an hipoteticai observer walking through there